Patriarchal Hegemony in the Novel “Women at Point Zero” by Nawal El Saadawi - Istifadah Istifadah; Wahyu Indah Mala Rohmana (Yayasan Visi Intan Permata, 2022)
This study aims to describe and analyze the forms of patriarchal hegemony in the novel Woman at Point Zero by Nawal El Saadawi. The patriarchal hegemony is then correlated with the teachings of Islam, which are often seen as supporting the domination of men. It is a literary criticism that analyzes and interprets literary work. Sylvia Walby’s six structures of patriarchy theory and Gramsci’s theory were used to analyze the data. The data were taken from the written work of Woman at Point Zero English Translation published in 2007. Data were taken by identifying, classifying, and analyzing the data by decoding them with the theories. The result of this study shows the variety of gender injustice and biases in the form of physical, verbal, sexual abuse, marginalization, and exploitation of women in the work. The implication of the research is to provide concrete evidence that Islamic teaching never provokes man domination and patriarchal practices over the woman.